“La protección jurídica de los saberes tradicionales de los pueblos originarios de la Amazonía Ecuatoriana” - María José, Vera Ostaiza (2019)
Traditional knowledge in the native peoples of the Ecuadorian Amazon, are constituted in a tangible and intangible wealth that Ecuador has, are knowledge that for thousands of years have been transmitted from generation to generation; Ancestral practices that have been applied in agriculture, social organization, medicine, construction, coexistence, etc., for these reasons, their legal protection is essential for the conservation and dissemination of this type of non-experimental science. Under this background, the present investigation, which is entitled: "THE LEGAL PROTECTION OF TRADITIONAL KNOWLEDGE OF THE ORIGINARY PEOPLES OF THE ECUADORIAN AMAZON," are intended to describe through the application of research instruments why legal protection guarantees The right to intellectual property of the traditional knowledge of the original peoples of the Ecuadorian Amazon, to determine whether compliance with current regulations is effective, to achieve this general objective, a doctrinal, legal and critical study of protection was carried out legal knowledge of the traditional knowledge of the native peoples of the Ecuadorian Amazon and their intellectual property; The results of the investigation determine that there are sufficient national and international laws that guarantee the legal projection of the traditional knowledge of the native peoples of the Ecuadorian Amazon, however, these regulations are not being properly applied, which is why many knowledge Traditional methods have been patented by transnationals, foreigners and settlers who, in essence, are not the creators of ancestral knowledge, these foundations indicate that legal protection and the right to intellectual property